A cAbl-MRTF-A Feedback Loop Contributes to Hepatic Stellate Cell Activation - Lu, Yunjie; Lv, Fangqiao; Kong, Ming; Chen, Xuyang; Duan, Yunfei; Chen, Xuemin; Sun, Donglin; Fang, Mingming; Xu, Yong (Frontiers in Cell and Developmental Biology, 2019)
Trans-differentiation of quiescent hepatic stellate cells (HSC) to myofibroblasts is a hallmark event in liver fibrosis. Previous studies have led the discovery that myocardin-related transcription factor A (MRTF-A) is a key regulator of HSC trans-differentiation or, activation. In the present study we investigated the interplay between MRTF-A and c-Abl (encoded by Abl1), a tyrosine kinase, in this process. We report that hepatic expression levels of c-Abl were down-regulated in MRTF-A knockout (KO) mice compared to wild type (WT) littermates in several different models of liver fibrosis. MRTF-A deficiency also resulted in c-Abl down-regulation in freshly isolated HSCs from the fibrotic livers of mice. MRTF-A knockdown or inhibition repressed c-Abl in cultured HSCs in vitro. Further analyses revealed that MRTF-A directly bound to the Abl1 promoter to activate transcription by interacting with Sp1. Reciprocally, pharmaceutical inhibition of c-Abl suppressed MRTF-A activity. Mechanistically, c-Abl activated extracellular signal-regulated kinase (ERK), which in turn phosphorylated MRTF-A and promoted MRTF-A nuclear trans-localization. In conclusion, our data suggest that a c-Abl-MRTF-A positive feedback loop contributes to HSC activation and liver fibrosis.